The Influence of Motivation and Organizational Culture on Employee Commitment at Kyriad Bumiminang Hotel - Vebbi Ilfian; Youmil Abrian (Journal of Multidimensional Management, 2024)
The purpose of this study is to analyze the Influence of Moivation and Organizational Culture on Employee Commitment at the Kyriad Bumiminang Hotel. This type of research is quantitative descriptive using the survey method. The sampling technique uses non-probability sampling. The sample used is a saturated sample, a saturated sample is a sampling technique when all populations are used as samples. The sample used was all operational employees at the Kyriad Hotel Bumiminang Padang, totaling 41 people. The data obtained were described, then a description of the research results was carried out using the TCR and SPSS techniques. Based on the results of the study, the Influence of Moivation and Organizational Culture on Employee Commitment at the Kyriad Bumiminang Hotel is seen from: the motivation variable is categorized as good at 3.4, the visiting variable of organizational culture is categorized as very good at 3.32, and the commitment variable is categorized as good at 3.33. the regression equation is Y = 24.111 + 0.110X1 + 0.176X2, and the F test value in this multiple linear regression analysis is 12.375 with a p-value of 0.000 which is smaller than 0.05 (significant) and an Adj.R square value of 0.322.